Opioid tolerance in methadone maintenance treatment: comparison of methadone and levomethadone in long-term treatment. Issue 1 (December 2016) - Gutwinski, Stefan; Schoofs, Nikola; Stuke, Heiner; Riemer, Thomas; Wiers, Corinde; Bermpohl, Felix
Abstract Background This study aimed to investigate the development of opioid tolerance in patients receiving long-term methadone maintenance treatment (MMT). Methods A region-wide cross-sectional study was performed focusing on dosage and duration of treatment. Differences between racemic methadone and levomethadone were examined. All 20 psychiatric hospitals and all 110 outpatient clinics in Berlin licensed to offer MMT were approached in order to reach patients under MMT fulfilling the DSM IV criteria of opiate dependence. In the study, 720 patients treated with racemic methadone or levomethadone gave information on the dosage of treatment. Out of these, 679 patients indicated the duration of MMT. Results Treatment with racemic methadone was reported for 370 patients (54.5 %), with levomethadone for 309 patients (45.5 %). Mean duration of MMT was 7.5 years. We found a significant correlation between dosage and duration of treatment, both in a conjoint analysis for the two substances racemic methadone and levomethadone and for each substance separately. These effects remained significant when only patients receiving MMT for 1 year or longer were considered, indicating proceeding tolerance development in long-term treatment. When correlations were compared between racemic methadone and levomethadone, no significant difference was found. Conclusions Our data show a tolerance development under long-term treatment with both racemic methadone and levomethadone. Tolerance development did not differ significantly between the two substances.